Effects of Home Blood Sugar Monitoring on HbA1c Among Diabetes Mellitus Patients Attending a Tertiary Care Hospital in Peshawar: Effects of Home Blood Sugar Monitoring on HbA1c Levels - Shah, Syed Abdullah; Ahmad, Shahwar; Bilal, Muhammad; Khan, Younas Nazir; Ullah, Shafiq; Khan, Muhammad Tariq Humayun (Pakistan Journal of Health Sciences, 2025)
Diabetes mellitus (DM), encompassing both type 1 and type 2, has escalated worldwide over the last twenty years, resulting in elevated death and morbidity rates. Prior research indicates that home blood glucose monitoring enhances metabolic control and aids in alleviating the atherosclerotic effects of type 2 diabetes mellitus. Objectives: To evaluate the effect of home blood glucose monitoring on HbA1c levels among diabetic patients at Lady Reading Hospital (LRH), Peshawar. Methods: This quasi-experimental study was performed over six months in the Department of General Medicine at LRH, Peshawar, including 62 diabetic patients. Participants were directed to assess fasting blood glucose thrice weekly for three months, maintaining their existing medical care. HbA1c was measured before and during the intervention. Means and standard deviations were used to evaluate continuous variables in SPSS version 22.0. A paired t-test was used to compare pre- and post-intervention mean HbA1c levels, with p < 0.05 indicating statistical significance. Results: The mean age of participants was 45 ± 12.29 years, with 61% male and 39% female. The average diabetes duration was 10 ± 5.8 years. Pre-monitoring HbA1c was 9.62 ± 1.87%, which significantly reduced to 8.02 ± 1.19% after three months (mean difference=1.6%, p=0.0001). Significant reductions were observed across all age groups, genders, weight categories, and diabetes durations (p<0.05). Conclusions: Home blood glucose monitoring significantly improves glycemic control in diabetic patients, as evidenced by the reduction in HbA1c levels, consistent across various demographics.